1991
DOI: 10.1038/bjc.1991.258
|View full text |Cite
|
Sign up to set email alerts
|

The antileukaemic activity of 5-Aza-2 deoxycytidine (Aza-dC) in patients with relapsed and resistant leukaemia

Abstract: In the present study we demonstrate that Aza-dC in combination with Amsacrine has major antileukaemic properties in patients who have not already received extensive Ara-C therapy. Eight out of 11 patients in their first relapse of acute leukaemia achieved complete remission. Cross resistance between Ara-C and Aza-dC was revealed by the lack of antileukaemic activity in five patients with with Ara-C resistant leukaemia. Combination therapy with Aza-dC/Ams-acrine induced a considerable period of a granulocytopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 7 publications
0
23
0
1
Order By: Relevance
“…Recent reports support the hypothesis on conventional chemotherapy. [5][6][7] In addition, 5-Aza-CdR has that RAR␀ is a tumor suppressor gene. 25,26 shown clinical activity in patients with myelodysplastic synThe role of most tumor suppressor genes in the pathogenesis action is also schedule-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports support the hypothesis on conventional chemotherapy. [5][6][7] In addition, 5-Aza-CdR has that RAR␀ is a tumor suppressor gene. 25,26 shown clinical activity in patients with myelodysplastic synThe role of most tumor suppressor genes in the pathogenesis action is also schedule-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…19 Several studies have demonstrated the efficacy of decitabine in patients with recurrent or refractory leukemia. 20 The dose-limiting toxicity of decitabine in early Phase I trials was prolonged myelosuppression with minimal extramedullary toxicity. 21,22 In a Phase I study, decitabine was given at a dose of 50 -100 mg/m 2 every 12 hours for 5 days to 130 patients with CML.…”
Section: Hypomethylating Agents (Decitabine and 5-azacytidine)mentioning
confidence: 99%
“…Inhibitors that can a ect corepressor function such as AZAdC and TSA have been successfully used in clinical trials to treat patients with leukemia and myelodysplastic syndromes (Lubbert, 2000;Limonta et al, 1993;Richel et al, 1991). However, details on the molecular mechanisms underlying gene repression and the e ects of AZAdC and TSA on APL blasts are currently scars or missing.…”
Section: Repression Of An Erythroid Enhancermentioning
confidence: 99%